Prognostic significance of c-erbB-2 expression in node negative breast cancer. - Bianchi, S. (Nature Publishing Group, 1993)
The prognostic value of c-erbB-2 oncogene expression was studied retrospectively in a consecutive series of 230 node negative breast cancers, followed-up for at least 7 years after primary treatment. The expression of c-erbB-2 oncoprotein was determined on formalin-fixed paraffin-embedded tissue, using a monoclonal anti-c-erbB-2 antibody by the avidin-biotin immunoperoxidase method. Positive immunostaining was observed in 20.9% of cases, whereas strong diffuse positivity was recorded only in 8.7% of cases. C-erbB-2 gene product showed no association to T category or nuclear grade. A significant association of c-erbB-2 expression to prognosis was observed only for cases showing a strong diffuse immunostaining, but such an association was no longer statistically significant at multivariate analysis adjusting for other prognostic factors such as T category and nuclear grading. C-erbB-2 expression is of no value to predict the clinical course of node negative patients in the current practice. IMAGES: